Phenotypic and molecular characterization of croaker, a new mating behavior mutant of Drosophila melanogaster. - Yokokura, T.; Ueda, R.; Yamamoto, D. (Japanese Journal of Genetics [Idengaku Zasshi], 1995)
Mating of Drosophila melanogaster is a stereotypically patterned behavior consisting of a fixed sequence of actions that is primarily under genetic control. Although courtship can be easily monitored and quantified, little is known about its neural basis. To obtain a better understanding of cellular and molecular mechanisms underlying courtship, we have isolated mutants that disrupt specific aspects of mating behavior. The croaker mutant was isolated from approximately 1,000 lines harboring single P-element insertions by screening for aberrant courtship song: croaker males often generate polycyclic pulse song while most of the song pulses are monocyclic in the wild-type. The mutant is also defective in flight. Intracellular recordings of excitatory junction potentials from larval body wall muscles and Ca++ action potentials from adult indirect flight muscles demonstrated that neuromuscular transmission and Ca++ electrogenesis in the muscle fibers are not impaired by the croaker mutation. To define the croaker gene molecularly, genomic DNA surrounding the P-element insertion site was cloned by plasmid rescue and subsequent screening of a cosmid library. Northern blotting with the genomic DNA probes detected three transcripts in the wild-type, which were not expressed in the croaker mutant.